Ethnopharmacological study of medicinal plants used against skin ailments on Mount Pelion, central Greece - Tsioutsiou, Efthymia Eleni; Cheilari, Antigoni; Aligiannis, Nektarios (Frontiers in Pharmacology, 2023)
Throughout centuries, traditional herbal medicine and the employment of medicinal plants have constituted an important tool for the treatment and prevention of numerous diseases. The present study focuses on the collection of ethnopharmacological data regarding the uses of medicinal plants for the treatment of dermatological ailments in various villages of Mount Pelion, Greece. More specifically, the study area is represented by the city of Volos and villages located in Central West Pelion and has not been investigated up to now. The information on the medicinal uses of the various species was obtained through extensive semi-structured interviews or the completion of specific questionnaires by the informants. Although the Covid-19 pandemic caused difficulties and obstacles in carrying out this research procedure, 60 informants were recruited and interviewed (36 women and 24 men). Their age range was between 31 and 97 years and their educational level was characterized by great diversity (primary, secondary, and higher education). The elaboration of the gathered information included the calculation of some quantitative indices, such as Fidelity Level (FL), and Informant Consensus Factor (FIC). Moreover, the relative importance of each reported species was identified by calculating the Use Value (UV). The interviews revealed 38 plant taxa belonging to 27 plant families reported to be used in the study area exclusively against skin diseases. The plant family mostly mentioned by the informants was Hypericaceae, followed by Plantaginaceae and Amaryllidaceae, while among the most popular methods of application are cataplasms, compresses, and topical application of decoction or raw plant material. Some of the most cited species are Hypericum perforatum L., Quercus coccifera L., and Plantago sp., traditionally used to treat skin problems such as eczema, wounds, and insect stings. The present ethnopharmacological study is the first documentation of ethnobotanical knowledge of this area that points out the traditional uses of medicinal plants against skin ailments.